2012
DOI: 10.1002/pmic.201200376
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the maternal protein restriction rat model for schizophrenia: Identification of translational changes in hormonal signaling pathways and glutamate neurotransmission

Abstract: Previous studies have found that some first onset schizophrenia patients show signs of impaired insulin signaling. Also, epidemiological studies have shown that periods of suboptimal nutrition including protein deficiencies during pregnancy can lead to increased incidence of metabolic conditions and psychiatric disorders in the offspring. For these reasons, we have carried out a molecular profiling analysis of blood serum and brain tissues from adult offspring produced by the maternal low protein (LP) rat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…An association of IUGR, induced by either food deprivation or ligature of uterine vessels, and disturbances in the GABAergic system has been previously suggested by the finding of reduced glutamate decarboxylase activity in several brain regions [40, 41]. A proteomic approach has shown altered glutamate metabolism in the adult frontal cortex of a maternal low protein diet rat model [42]. We have previously shown that both hypothalamic and serum levels of glutamate were decreased in male rats submitted to IUGR [19].…”
Section: Discussionmentioning
confidence: 99%
“…An association of IUGR, induced by either food deprivation or ligature of uterine vessels, and disturbances in the GABAergic system has been previously suggested by the finding of reduced glutamate decarboxylase activity in several brain regions [40, 41]. A proteomic approach has shown altered glutamate metabolism in the adult frontal cortex of a maternal low protein diet rat model [42]. We have previously shown that both hypothalamic and serum levels of glutamate were decreased in male rats submitted to IUGR [19].…”
Section: Discussionmentioning
confidence: 99%
“…Since synapsin supports presynaptic contact (Han et al, 1991; Melloni et al, 1994), its lysis should accompany axon removal. Interestingly, OPN/synaptic interaction exists in schizophrenia, where aberrant hypothalamic connectivity maps with altered OPN (Guest et al, 2012). It should be noted that lack of KO effect on MAP1B and N-cadherin could be due to survival interval examined, since expression of each protein is more fluid during later degeneration/regeneration transition (Popa-Wagner et al, 1999; Takeichi and Abe, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Labelling-based and label-free quantitative methods have shown that proteins mainly involved in neurotransmission (i.e. glutamatergic pathways), cytoskeletal components (actin, myosin light chain) and synaptic remodelling (calcium-transporting ATPase, cAMP-dependent protein kinase, guanine nucleotide-binding proteins subunits and RAS-related proteins) are differentially expressed in schizophrenia [163,164]. 2DE proteomic approaches have been also undertaken for schizophrenia and bipolarity [165] and anxiety disorders [166], revealing changes in proteins involved in neurotransmission (as septins), energy metabolism (metabolic or mitochondrial-associated proteins) and oxidative stress-related networks.…”
Section: The Proteome Of the Brain Proteomic Studies Of Neurodegenermentioning
confidence: 99%